The Psychological Conflicts in the Film in the Heart of the Sea (2015): A Psychological Approach - Utomo, Danang (LPPM Universitas Jambi, 2023)
This study aims to analyze a psychological conflict experienced by the crew of the Essex ship in the film in the heart of the sea (2015) which is based on the legend of the Moby Dick. In this study, researchers used the behavioristic of John Broadus Watson. This research is included in qualitative research with a focus on the relation between literature and psychology by means of psychological criticism in categories such as psychoanalysis the author, reader and text also the Psychology and the creative process, Psychoanalysis and biography by using psychoanalysis. The data analysis technique in this research is descriptive analysis. From this study, found findings based on the formulation of the problem. First, what behavior can be observed in the psychological conflicts that occur in the crew of the Essex ship. . According to Watson, the only meaningful data in psychology is behavior that can be observed and measured objectively. Second, how the environment can generate the behavior of the characters. Watson believed that behavior is the result of the environmental factors that influence an individual’s learning and experience. Watson emphasized the role of conditioning, or the process of learning through association, in shaping behavior. What the crew of the Essex ship experienced in the movie